A never-before opportunity to strengthen investment and action on adolescent contraception, and what we must do to make full use of it - Venkatraman Chandra-Mouli; Pooja S. Parameshwar; Matti Parry; Catherine Lane; Gwyn Hainsworth; Sylvia Wong; Lindsay Menard-Freeman; Beth Scott; Emily Sullivan; Miles Kemplay; Lale Say (BMC, 2017)
Abstract Background Increasingly, the health and rights of adolescents are being recognized and prioritized on the global agenda. This presents us with a "never-before" opportunity to address adolescent contraception. This is timely, as there are enormous numbers of adolescents who are currently unable to obtain and use contraceptives. From research evidence and programmatic experience, it is clear that we need to do things differently to meet their needs/fulfil their rights. Main body In this commentary, we call for action in several key areas to address adolescents' persistent inability to obtain and use contraceptives. We must move away from one-size-fits-all approaches, from a 'condoms-only' mind set, from separate services for adolescents, from ignoring the appeal of pharmacies and shops, and from one-off-training to make health workers adolescent friendly. Our efforts to expand access to quality contraceptive services to adolescents must be combined with efforts to build their desire and ability to use them, and to do so consistently. In order for these changes to be made, action must be taken on several levels. This includes the formulation of sound national policies and strategies, robust programme implementation with monitoring, regular programmatic reviews, and implementation research. Further, high-quality collection, analysis, and dissemination of data must underlie all of our efforts. As we move ahead, we must also recognize and draw lessons from positive examples of large scale and sustained programmes in countries that have led the way in increasing contraceptive use by adolescents. Conclusion This unprecedented moment in history gives us a real opportunity to bring about transformational change, particularly when there is so much at stake.